KAJIAN TENTANG SEBARAN SAMPAH KABUPATEN BANYUMAS - SUSATYO ADHI PRAMONO; BASUKI BASUKI (Teodolita: Media Komunkasi Ilmiah di Bidang Teknik, 2021)
ABSTRACT (ABSTRAK) Data collection on solid waste, volume, characteristics and means of transporting waste in all areas of Banyumas Regency, is absolutely necessary as the first step in determining waste management policies. This study aims to measure waste generation in Banyumas district. Measurements were carried out in 27 subdistricts in Banyumas district. Waste is grouped into 2 categories, namely organic waste and inorganic waste. From the results of this study, it can also be calculated the amount of waste generated that has not been transported to the TPA. Keywords: Garbage, Banyumas Pendataan mengenai persampahan, volume, karakteristik dan sarana pengangkut sampah di seluruh wilayah Kabupaten Banyumas, mutlak diperlukan sebagai langkah awal penentuan kebijakan pengolahan sampah Penelitian ini bertujuan mengukur timbulan sampah di kabupaten Banyumas. Pengukuran dilakukan di 27 kecamatan yang berada di kabupaten Banyumas. Sampah dikelompokkan dalam 2 katagori, yaitu sampah organik dan sampah anorganik. Dari hasil penelitian tersebut juga dapat dihitung jumlah timbulan sampah yang belum teragkut ke TPA. Kata kunci: Sampah, Banyumas